Two-year follow-up of gait and postural control following initiation of recombinant human tripeptidyl intracerebroventricular enzyme replacement therapy in two atypical CLN2 patients - Rahul Soangra; Marybeth Grant-Beuttler; Harriet Chang; Raymond Y. Wang (Scientific Reports)
Abstract Neuronal ceroid lipofuscinosis type 2 (CLN2) is a rapidly progressive neurodegenerative disorder leading to premature mortality. Ambulatory CLN2 patients typically receive standard of care treatment through biweekly intracerebroventricular (ICV) enzyme replacement therapy (ERT) involving recombinant human tripeptidyl peptidase 1, known as cerliponase alfa (Brineura®, Biomarin Pharmaceuticals). This study longitudinally assessed the impact of ICV cerliponase alfa ERT on gait, and postural control across a two-year span in two siblings diagnosed with atypical CLN2 disease. Both participants, ID01 (18 years and 8 months old at enrollment) and ID02 (13 years and 3 months old at enrollment), exhibited symptomatic characteristics which were studied longitudinally over three years. Their evaluations assessed postural sway variability, potential for slips and trips, gait metrics, sit-to-stand durations, scores from the sensory organization test (SOT), and gross motor function measure (GMFM) scores. Findings indicated a decline in postural complexity and stability in the medial-lateral (ML) axis, a reduction in toe clearance, and an augmented risk of stumbling for the participants. Over the two-year period of ERT, both siblings exhibited a progressive decline in walking velocity, characterized by reductions in step length and prolonged gait cycle time. The elder sibling demonstrated a notable increase in double support duration, indicative of heightened reliance on proprioceptive input to maintain stability during ambulation. Additionally, sit-to-stand times lengthened for siblings, further reflecting declines in motor function. Despite these challenges, SOT scores showed improvement after two years of ERT, suggesting some preservation of sensory integration. These findings in SOT scores indicate that cerliponase alfa treatment in patients with atypical CLN2 disease may confer benefits in postural stability, lower extremity strength, and ankle stiffness. However, declines in more complex motor functions, including sit-to-stand performance and postural complexity, persist, underscoring the progressive nature of the disease despite ongoing therapeutic intervention.